ANALISIS PENEMPATAN PEGAWAI PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN KEPULAUAN MERANTI TAHUN 2015 - Ansori, Putra Budi; Makrifat, Arief (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
The research was conducted at the Department of Transportation, Communication and Information Kab. Meranti Islands. The purpose of this study was to determine the placement analysis Officer at the Department of Transportation, Communication and Information Kab. Meranti Islands. The data used are primary data and secondary data by direct observation, questionnaire questionnaires and interviews. Furthermore, there are six (6) indicators that could be used to do the analysis, namely: education, work experience, education and training, work ability, physical condition and menta and seniorital. System analysis of the data in this study using deskiptif research, namely analyzing data that has been acquired and associated with theories that support discussions by using Guttman scale. Guttman scale is a scale used to answer that is clear (firm) and consistent like: Sure-not Sure, Yes-No, True-False, Positive Negative, and so forth. In this study, the authors use a Yes-No choice, with the score lowest score is 0 (for respondents who expressed no) and scores the highest value is 1 (for respondents who stated yes). Total population in this study were all employees of the Department of Transportation, Communication and Information Kab. Meranti Islands as many as 45 employees, while the total sample of 43 people. Further results were obtained from 6 (six) are 5 (five) indicator approach is not appropriate, the indicators of education, work experience, education and training, work ability and seniority because it is in the range 0.01 to 0.49, with the percentage by 28%, 44%, 38%, 48%, 48%, whereas one (1) indicator is approaching the appropriate physical and mental konsisi indicator which is in the range from 0.51 to 0.99 with a percentage of 73%.